Studi Tentang Kebudayaan Islam pada Masa Khulafaur Rasydin - Haidar Putra Daulay; Sholihah Titin Sumanti (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
Khulafaur Rasyidin is a special nickname for the four friends who replaced the leadership of the Muslims after the death of Rasulullah Saw, so in carrying out this leadership there are developments and challenges in managing government both from geopolitics, social, education, economics, architecture and art as well as the expansion of Islamic power which is where has become a study of Islamic culture starting from 632 AD to 661 AD or 11 Hijriah to 40 Hijriah.